The effects of contrast bathing and compression therapy on muscular performance - French, D. N.; Thompson, K. G.; Garland, S. W.; Barnes, C. A.; Portas, M. D.; Hood, P. E.; Wilkes, G. (Medicine & Science in Sports & Exercise, 2008)
Contrast bathing (CB) and compression garments (CG) are widely used to promote recovery.